2005
DOI: 10.1002/jso.20188
|View full text |Cite
|
Sign up to set email alerts
|

Management of midgut carcinoids

Abstract: Midgut carcinoids developing in the small intestine represent the most common cause of the carcinoid syndrome, with severe symptoms of flush, diarrhoea, and fibrotic valvular heart disease. The tumours may be histologically identified with specific chromogranin A or synaptophysine immunostainings, and by serotonin reactivity, which supports a midgut origin. Urinary 5-HIAA excretion and serum chromogranin A measurements are used as biochemical tumour markers for clinical diagnosis, and as important monitors of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
66
1
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(71 citation statements)
references
References 44 publications
3
66
1
1
Order By: Relevance
“…Nevertheless, the optimal approach remains unclear as the biological behavior of these NETs remains largely unknown (30,31). Although ileum/jejunum NETs often present with metastases at diagnosis, surgical treatment has become increasingly important for their management (32). For patients presenting with tumors in the jejunum/ileum, surgical resection of the bowel with regional lymphadenectomy is recommended (30).…”
Section: Management Of Localized Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, the optimal approach remains unclear as the biological behavior of these NETs remains largely unknown (30,31). Although ileum/jejunum NETs often present with metastases at diagnosis, surgical treatment has become increasingly important for their management (32). For patients presenting with tumors in the jejunum/ileum, surgical resection of the bowel with regional lymphadenectomy is recommended (30).…”
Section: Management Of Localized Diseasementioning
confidence: 99%
“…The surgical procedure should include careful examination of the entire bowel, because multiple synchronous lesions may be present. Surgery at an early stage of the disease is favorable when growth is less extensive in the mesentery (32,34). Colon NETs should be treated with an appropriate right or left-sided hemicolectomy or sigmoidectomy (35).…”
Section: Management Of Localized Diseasementioning
confidence: 99%
“…Besides CT scanning, CT enteroclysis or MRI enteroclysis are the most widely used radiological imaging techniques specifically used to localize NETs of the small bowel [39] . CT scanning of the abdomen and thorax as well as somatostatin receptor scintigraphy are the major imaging modalities used to establish tumor staging and localization initially [13,14,40,41] . 68-Gallium-DOTATOC-PET/CT is a new, very sensitive method for visualizing (metastatic) intestinal NETs [42][43][44] ; however, this costly technique is not available everywhere.…”
mentioning
confidence: 99%
“…The suggestion is that resection of regional disease delayed onset of the obstruction and ischemia frequently seen in later stages of the disease. Although these data are biased because of surgical selection, it does appear that aggressive surgical resection of regional disease may improve palliation in these patients, who are often experiencing ischemic symptoms 38,40 . Furthermore, some investigators have retrospectively shown an improved median pfs of 56 months compared with 25 months in patients whose primary tumour was resected in the face of advanced liver disease 41 .…”
Section: Summary Of Evidencementioning
confidence: 99%